Komposisi asid lemak dalam beberapa masakan Melayu berasaskan ayam,lembu,ikan dan telur - Shahida M.; Suriah A.R; Mohd khan A.; Ayub M.Y; Osman H. (Universiti Kebangsaan Malaysia, 2009)
A survey on fat intake and fatty acid in the diet was carried out among Malay population in Klang Valley. The objective of this study was to determine the fatty acid content of chicken, meat, fish and egg dishes consumed by the subjects surved. Food sample obtained from subject were analyzed for fatty acid content using gas chromatography. Result from food sample analysed showed the mean content of saturated fatty acid (SFA) (Fish 3.06±1.85 g/100g, egg 2.64±1.68 g/100g and meat 2.50±2.42 g/100g) and monounsaturated fatty acid (MUFA) of the fish (2.34±2.16 g/100g), egg (2.49±1.37 g/100g) and meat (2.31±2.27 g/100g) dishes were high, while the mean value of polyunsaturated fatty acid in fish dishes (0.82±0.57g/100g) were higher compared to chicken (0.7±0.29 g/100g), meat (0.43±0.63 g/100g) and egg dishes (0.43±0.43 g/100g). All dishes did not have balanced ω6:ω3 ratio. As a conclusion, dishes that contained high polyunsaturated fatty acid and balanced ω6:ω3 is a healthy diet.